ARTI DAN MAKNA KEBENARAN ILMIAH DALAM TELAAH HUKUM ISLAM - Gazali HB, Ahmad (Universitas Islam Negeri Antasari Banjarmasin, 2013)
This writing is the description about the scientific truth of the Islamic Law, or in the Islamic science treasury is called Fiqh. Through the scientific process, we can find out lots theories of truths, for instant the correspondent, coherent, pragmatic, syntactic, semantic, non descriptive and over logic truth. Toward those theories of truth, there are three approach methodologies that we can apply to get them. The first methodology is the religious approach, the second one is the scientific approach, and the last one is the philosophic approach. These three approach methodologies are closely relates with the development of the Islamic Law, since they are also the scientific disciplines. In the Islamic Law, there is also mention about the correspondence and coherence truth. The methodology that is used to result the laws related to the general scientific methodology as well. For that reason, the truth which is resulted from that scientific approach is mostly positive